Test Study on Airtight Capability of Filter Cakes for Slurry Shield and Its Application in a Case - Fanlu Min; Wei Zhu; Shengquan Xia; Rui Wang; Daiwei Wei; Teng Jiang (Advances in Materials Science and Engineering)
To learn the airproof capacity of filter cakes as opening chambers under air pressure, a series of tests were carried out. The variations of discharged water with air pressure and time were observed, and the relationship between airproof capacity of filter cakes and surrounding air pressure was analysed. The test results indicated that there were three stages as compressed air acting on filter cakes: completely not infiltration, a very small amount of infiltration, and penetration leakage. The certain air pressure between the first and second stages was called the airproofing value of filter cake. And a capillary bundle model was used to explain the mechanism of air tightness of filter cakes. In Nanjing Yangtze River Tunnel, a 5 cm thickness filter cake was formed in gravel sand, and its airproofing value was a little lower than 0.12 MPa. The air pressure used as opening chamber should be equal to the summation of water pressure in sand and airproofing value of filter cake. While the air pressure is larger than the summation, the filter cake would be gas permeable. The slurry formulation and airproofing value of filter cakes obtained in the tests were applied successfully in Nanjing Yangtze River Tunnel.